Evaluating the Effective Use of Electronic Journals by the Academia: A Study - Nikam, Khaiser; Kumar, Dhruva (DESIDOC Journal of Library & Information Technology, 2013)
Users’ studies are one of the most prominent areas of research in library and information science. Now the trend is to examine the use of e-libraries, e-journals and e-databases. Many studies have been carried out both in India and abroad in this area. This study aims to examine the user behaviour of 66 out of 100 research scholars and faculty members of select departments at the University of Mysore like environmental science, sericulture science, zoology and genetics form the sample. Structured questionnaire with 5 point scale was used and the mean and SD values were calculated using SPSS. The major findings are: Users use both print and electronic sources of information. Majority of the respondents have learnt to use e-journals effectively from ‘friends/colleagues’. The respondents ‘look for quality controlled scientific and scholarly journals’. Respondents identify relevant electronic articles by ‘browsing through recent issues’ (mean=3.39) followed by ‘searching full-text databases from publishers or aggregator’ (e.g. Elsevier, Springer). http://dx.doi.org/10.14429/djlit.33.2.4200